Wastes to be the source of nutrients and energy to mitigate climate change and ensure future sustainability: options and strategies. (2nd April 2020) - Ahmed, Mukhtar; Ahmad, Shakeel; Tariq, Muhammad; Fatima, Zartash; Aslam, Zohra; Raza, Muhammad Ali; Iqbal, Nasir; Akmal, Muhammad; Hassan, Fayyaz-ul-; Abbasi, Nadeem Akhtar; Hayat, Rifat
Abstract: Waste production is associated with human inhabitation and its rate is increasing over time. Globally, the major proportion of waste is disposed of through landfilling and open dumping, which is environmentally unsafe due to emission of greenhouse gases (GHGs). Thus, in order to avoid emission of GHGs from wastes it is important to use techniques that can convert wastes to energy/nutrients on eco-friendly economical way. Furthermore, quantification of the impacts of these waste management techniques on ecosystem is also needed through the application of tools like modeling, remote sensing, geographical information system (GIS), Unmanned Aerial Vehicles (UAVs) and life cycle assessments (LCA). Thus, this review was conducted by considering focus on potential of nutrient and energy recovery techniques from various types of wastes and approaches to enhance the efficiency of the process. The outcomes depicted that the aerobic and anaerobic digestion is suitable to deal with biodegradable and organic fraction of the waste, but anaerobic digestion seem to be more sustainable waste management techniques. Additionally, the review covers the techniques to drive energy and recover nutrient from non-biodegradable proportion. Different modern analytical tools; such as remote sensing, GIS and simple/dynamic models could be useful tool to help in the decision-making processes for waste managements. These tools can help us to design integrated solid waste management processes. Finally, we suggest that LCA should be considered to determine the environmental load of material/product from its production to final disposal (from cradle to grave).